Preparation and Characterization of NiTi/PVA Nanofibers by Electrospinning - Akram Jabur; Randa Al-Tuhafi (Engineering and Technology Journal, 2021)
NiTi alloys are widely used in biomedical applications for their unique properties particularly the shape memory effect, superelasticity, and biocompatibility. In this research, NiTi/PVA composite nanofibers are fabricated by electrospinning technique, using a novel method of producing NiTi ultrafine particles by immersing amorphous NiTi alloy in dilute aqua regia solution. The NiTi particles are successfully embedded in the PVA matrix. The produced NiTi particles are analyzed by X-ray diffraction (XRD), Energy dispersive spectroscopy (EDS), and Particle size analyzer. The XRD pattern of ultrafine NiTi particles shows much better phases as compared to the XRD pattern of the amorphous NiTi alloy sample. The morphology of the produced NiTi/PVA composite nanofibers are characterized by Field emission scanning microscope (FESEM), and Energy dispersive spectrometry (EDS). The test results show regular continuous smooth bead-free nanofibers.